Racial Discrimination Experienced by the Main Character in Malcolm Hansen's They Come in All Colors - Yahya, Achmad Choironi (Journal of Literature, Linguistics, & Cultural Studies, 2022)
This study aimed to examine the issue of discrimination as reflected in the novel They Come in All Colors. Discrimination against colored people arises because white people as the dominant group thought that their racial group was much better than the colored people in many aspects of social life. Thus, this study was a literary criticism that focused on the discrimination against colored people described in the novel. This study used a sociological approach to analyze Newman's five forms of discrimination as well as describe the types of discrimination responses from Joe R. Feagin and Melvin P. The data were taken from words, phrases, and sentences in the novel They Come in All Colors by Malcolm Hansen. The researcher collected the data by identifying and classifying relevant quotes in They Come in All Colors. Then, the researcher analyzed the data by explaining the data related to the theory. This study revealed that there were four forms of discrimination described in the novel, namely verbal expression, avoidance, exclusion, and physical abuse. On the other hand, there were types of responses to discrimination that were used to fight discrimination, which covered withdrawal, resign acceptance, verbal confrontation, and physical confrontation.